Modeling of Traditional Ceremonial Plants on The Tenggerese Residential House Front Yard - Irawan Setyabudi; Mochamad Syarif Hidayatullah; Dian Kartika Santoso (University of Merdeka Malang, 2026)
The Tenggerese community in Ngadas Village, Malang Regency, is renowned for its traditional ceremonies that utilize various plant species as ritual media. Over time, continuous use without conservation threatens the sustainability of these plants. This study aims to identify the types, functions, meanings, and growing requirements of ceremonial plants and to propose a front yard landscape model integrating these plants as a form of cultural landscape-based conservation. A descriptive qualitative method was employed through literature review, in-depth interviews with local elders and government representatives, and field observations. The results identified 26 ceremonial plant species, such as Cordyline fruticosa, Imperata cylindrica, and Gigantochloa apus, each with unique symbolic functions. Three typologies of front yard spaces were found: large (6x8 m), medium (3x6 m), and small (1x5 m), serving as the basis for adaptive landscape modeling. The modeling was developed using SketchUp, Lumion, and Adobe Photoshop. The study concludes that integrating ethnobotanical ceremonial plants into residential front yards can promote their conservation while visually reinforcing the cultural identity of the Tenggerese people.